Avaliação de sementes de variedades de milho em sistema de produção orgânica qualidade fisiológica e armazenabilidade das sementes - Abucarma, Vânia Marcia (2008)
The corn is one of the most cultivated cereals of the world, and the quality of the used seeds is important for the success of the tilling. One of the great problems of the organic agriculture is the supply of the seeds, and the improved variety becomes interesting because of being less demanding to inputs and presenting a good adaptation. The seeds of the variety of corn generally are produced in the property itself and the conditions of storage very often are not adapted compromising the quality of the seeds for near sowing. With that the objective of this work valued the physiologic potential and the storage of seeds of improved variety of corn, when they were produced in system of organic cultivation. The experiment was driven in the Laboratory of Seeds and Seedlings and in the sector of Cultivation When Prof Was Protected. Mário Cesar Lopes of the Universidade estadual do Oeste do Paraná (UNIOESTE), in the local authority of Naive Marshal Rondon, State of the Paraná. For evaluation of the physiologic quality of the seeds there was used the improved variety of corn OCEPAR 202, BRS 4150, Sun of the Morning and IPR 114, recently gathered and after the storage of five months in cold camera and room temperature The seeds were valued by the test of Germination; Mass of Mil Seeds; Degree of Moisture; Tetrazólio; Test of the Coldness; Emergence in Ground; Rate of the Speed of Germination; First counting of the Test of Germination; Length of the air Part of Plantules; Fresh Mass of the air Part of Plantules and Dry Mass of the air Part of Plantules. The experimental delineation was completely randomized with arrangement fatorial 4 x 3 and four repetitions. For the analysis of the results has shown that the improved varieties of maize, OCEPAR 202, BRS 4150, Sol da Manhã and IPR114 demonstrated high quality physiological. Five months in a controlled environment was the best condition for storing and cultivate Sol da Manhã had the best physiological quality in different forms of storage